2023
DOI: 10.1186/s13023-023-02629-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial implications of rare genetic skin diseases affecting appearance on daily life experiences, emotional state, self-perception and quality of life in adults: a systematic review

Abstract: Background Since the beginning of human genetic research, there are very few publications sharing insights of the negative impact of rare genetic skin diseases (RGSD) on patients’ experiences. This systematic review assessed the psychosocial implications of these conditions in terms of daily life experiences, emotional state, self-perception, and Quality of Life (QoL). Methodology A systematic review was carried out on albinism, neurofibromatosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 184 publications
(511 reference statements)
0
12
0
1
Order By: Relevance
“…Firstly, the themes we obtained align with the findings of a systematic literature review we conducted on the psychosocial implications of rare genetic skin diseases, including albinism [ 69 ]. We have found themes related to stigma and discrimination during childhood and adolescence, the importance of social support, genetic inheritance concerns, altered everyday functioning (e.g., mobility, skincare), difficulties with some healthcare providers, misconceptions and stereotypes in society, and a wide range of coping strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the themes we obtained align with the findings of a systematic literature review we conducted on the psychosocial implications of rare genetic skin diseases, including albinism [ 69 ]. We have found themes related to stigma and discrimination during childhood and adolescence, the importance of social support, genetic inheritance concerns, altered everyday functioning (e.g., mobility, skincare), difficulties with some healthcare providers, misconceptions and stereotypes in society, and a wide range of coping strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, moderate or severe impairment of physical health-related components of QoL were significant only for those aged 60 years or older, whereas moderate impairment of subjective and mental health-related components of QoL were significant for those aged 20–39 and 40–59 years, relative to those aged 19 years or younger. A systematic review [ 8 ] reported that NF1 can affect psychological well-being in patients, with more pronounced negative effects (e.g., depressive symptoms) on women than on men [ 19 ]. This may be due to the negative impact of NF1, such as cosmetic disfigurement, negative body image, and appearance-related concerns [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although detailed information about neurological symptoms was not included in the national database, progressive neurological symptoms, especially paralysis and pain, may more strongly deteriorate multiple components of QoL than other symptoms/lesions in patients with NF1. According to a previous systematic review [ 8 ], one of the most important characteristics of NF1 is the presence of acute/chronic pain and physical discomfort [ 22 ]. Neurological symptoms can disturb sleep and daily functioning and increase fatigue, leading to deterioration of “mobility,” “self-care,” and “usual activities” (e.g., job, studying) in patients with NF1.…”
Section: Discussionmentioning
confidence: 99%
“…That why is important to discuss of psychological effects associated with albinism and explore the psychosocial challenges faced by individuals with albinism. Patients with albinism need an early intervention, support systems, and inclusive policies to promote their well‐being and QoL 28,29 …”
Section: Albinismmentioning
confidence: 99%
“…Patients with albinism need an early intervention, support systems, and inclusive policies to promote their well-being and QoL. 28,29 Biology of skin. Pigments and melanocites.…”
Section: Albinismmentioning
confidence: 99%